THE EFFECTIVENESS OF FERMENTED MIXED SLAUGHTERHOUSE AND TOFU INDUSTRY WASTE ADDITION ON PEAT WATER THAT IS USED AS Chlorella sp. CULTURE MEDIA - Christina Lydia Singal; Budijono Budijono; M Hasbi M Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTPeat water has a low nutrient content, but it can be enriched by addition of fermented mixed slaughterhouse and tofu industry waste. This media may be used for growing Chlorella sp. The purpose of this study was to determine the effect of fermented mixed slaughterhouse and tofu industry waste as alternative nutrients for the growth of Chlorella sp. This study was conducted in September-October 2019. RAL method was applied with 5 different concentrations of mixed solution (50% tofu industry waste + 50% slaughterhouse waste), there were 600 ml/3L (P1), 1,200 ml/3L (P2), 1,800 ml/3L (P3), 2,400 ml/3L (P4) and 0 ml/3L (P5), with 3 repetitions. Parameters measured were Chlorella sp. abundance, nitrate and phosphate content. Results shown that Chlorella sp. grow well in all treatments, except control. The best result was provided by P4 (8.956 x 106 cells/ml) that was achieved on the 6th day. Nitrate and phosphate content decreased during the experiment, the nitrate was reduced by 16.026 mg/L or 87.3 %, while the phosphate was reduced by 18.347 mg/L or 82.2 %. Based on data obtained, it can be concluded that the peat water can be enriched by addition of fermented mixed slaughterhouse and tofu industry waste and it can be used as nutrients for growing Chlorella sp. Keywords: nutrient, liquid waste, microalgae, algae culture